2003
DOI: 10.1096/fj.02-0914fje
|View full text |Cite
|
Sign up to set email alerts
|

Dual mechanisms of green tea extract‐induced cell survival in human epidermal keratinocytes

Abstract: Beneficial effects attributed to green tea, such as its anticancer and antioxidant properties, may be mediated by (-)-epigallocatechin-3-gallate (EGCG). In this study, the effects of EGCG on cell proliferation and UV-induced apoptosis were investigated in normal epidermal keratinocytes. When topically applied to aged human skin, EGCG stimulated the proliferation of epidermal keratinocytes, which increased the epidermal thickness. In addition, this topical application also inhibited the UV-induced apoptosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(106 citation statements)
references
References 38 publications
6
93
0
5
Order By: Relevance
“…Another possible mechanism is green tea extract may affect the activity of dihydrofolate reductase, an enzyme that is needed by pathogenic bacteria to synthesize purine and pyrimidine as well as increase the thickness of the epidermis [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism is green tea extract may affect the activity of dihydrofolate reductase, an enzyme that is needed by pathogenic bacteria to synthesize purine and pyrimidine as well as increase the thickness of the epidermis [33] .…”
Section: Discussionmentioning
confidence: 99%
“…A significant reason for the great interest in EGCG is because of its remarkable effects in many in vitro and in vivo tumor model systems Singh et al, 2002;Chung et al, 2003;Gupta et al, 2003;Hastak et al, 2003). Part of this effect of EGCG appears to be because, at physiologically attainable concentrations, it induces apoptosis in cancer cells without affecting normal cells (Ahmad et al, 1997, 2000; Chen et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Epigallocatechin-3-gallate (EGCG), the major polyphenolic constituent present in green tea, has received much attention over the last few years, as a potential cancerchemopreventive and cancer-chemotherapeutic agent, possibly because of its wide range of effects on a number of cellular processes and efficacy in many tumor model systems (Singh et al, 2002;Chung et al, 2003;Gupta et al, 2003;Hastak et al, 2003). Our previous studies have shown that EGCG, at pharmacologically attainable concentrations, results in inhibition of cell growth, arrest of the cell cycle in G0/G1 phase and induction of apoptosis in some human carcinoma cells (Ahmad et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical constituents of green tea extracts were able to prevent the adherence of microbes with the intestinal walls and interfere with the cell division thus inhibiting growth and multiplication of microbes 31 . The green tea extract may affect the purine and pyrimidine synthesis in bacteria 32 . In addition to these reports are available that both green and black tea produced larger zone of inhibition (400 µg / ml) which supports our study 33 .…”
Section: Resultsmentioning
confidence: 99%